Partnerships launched - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
CTA recently signed partnership agreements with two independent sector organisations in Ethiopia and Madagascar for joint ventures in publishing and general information work. Emerging from a process of pilot studies on potential partnerships...